2019
DOI: 10.1007/s10534-019-00180-w
|View full text |Cite
|
Sign up to set email alerts
|

The anti-bacterial iron-restriction defence mechanisms of egg white; the potential role of three lipocalin-like proteins in resistance against Salmonella

Abstract: Salmonella enterica serovar Enteritidis ( S E) is the most frequently-detected Salmonella in foodborne outbreaks in the European Union. Among such outbreaks, egg and egg products were identified as the most common vehicles of infection. Possibly, the major antibacterial property of egg white is iron restriction, which results from the presence of the iron-binding protein, ovotransferrin. To circumvent iron restriction, S E synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Although the members of microbial communities are often described as commensals, the relationship between the host and a particular bacterial species can simply change to other forms of relationship as mutualistic or parasitic depending on the host’s genetic background, nutritional status, or co-infection of the host ( Belkaid and Harrison, 2017 ). One of the main aspects influencing the bacterial switch from commensal to pathogen is the availability of iron, which is strongly regulated by lipocalins ( Lechner et al, 2001 ; Goetz et al, 2002 ; Fluckinger et al, 2004 ; Julien et al, 2019 ). Iron is one of the essential nutrients for almost all aerobic organisms.…”
Section: Regulation Of Pathogens and Natural Microbiotamentioning
confidence: 99%
“…Although the members of microbial communities are often described as commensals, the relationship between the host and a particular bacterial species can simply change to other forms of relationship as mutualistic or parasitic depending on the host’s genetic background, nutritional status, or co-infection of the host ( Belkaid and Harrison, 2017 ). One of the main aspects influencing the bacterial switch from commensal to pathogen is the availability of iron, which is strongly regulated by lipocalins ( Lechner et al, 2001 ; Goetz et al, 2002 ; Fluckinger et al, 2004 ; Julien et al, 2019 ). Iron is one of the essential nutrients for almost all aerobic organisms.…”
Section: Regulation Of Pathogens and Natural Microbiotamentioning
confidence: 99%
“…When the outer protective system of an egg becomes compromised, the internal chemical defense mechanism plays a role [ 7 ]. Among the chemical defense mechanisms, the most important are various antibacterial proteins, especially lysozyme [ 8 ]. Egg white contains different proportions of antibacterial substances, mainly ovotransferrin, lysozyme, ovomucoid, and ovoid inhibitors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that genes involved in iron acquisition, cell envelope structure, osmotic and oxidative protection, amino acid and carbohydrate metabolism, motility, and stress responses may contribute to the survival of S. Enteritidis in egg albumen [ 31 , 33 , 34 , 35 ]. Egg white is a very unfavorable medium for bacteria, and the major factor limiting bacterial growth in it is iron restriction, having a concentration of iron between 3.6 and 18 µM [ 36 ]. Salmonella has the ability to produce siderophores in iron-restricted media to cope with this restriction, as in egg white, where iron is assumed to be chelated by ovotransferrin [ 37 ].…”
Section: Discussionmentioning
confidence: 99%